Distribution and contamination assessment of potentially harmful elements (As, Pb, Ni, Cd) in top soil of Penang Island, Malaysia - Abdul Hamid, F.A.Z.; Bakar, Ahmad Farid Abu; Ng, Tham Fatt; Ghani, Azman Abd; Mohamad Zulkifley, Mohamad Tarmizi (Springer Verlag (Germany), 2019)
This study discusses the distribution and contamination levels of potentially harmful elements (As, Pb, Ni, and Cd) in the urban top soil of Penang Island, one of the most important urban areas in Malaysia. The total surface area of Penang Island is 297 km2. Thirty-one surface soil samples (0–20 cm) were collected, digested and analysed using Inductively Coupled Plasma Mass Spectrometry (ICP-MS) for As, Pb, Ni, and Cd. The result showed that the mean concentrations of selected metals in soils were arranged in the following decreasing order: Pb > As > Ni > Cd. In terms of different soil types, soils derived from quaternary deposit have higher mean concentration of Pb, Ni, and Cd as compared to the granite residual soils which accumulate higher mean concentration of As. On the spatial distribution maps, As, Pb, Ni, and Cd are mainly concentrated in the north-to-north eastern areas of Penang Island and near to the main city, which are characterized by major residential and business areas. Thus, it suggests that the anthropogenic source is the main contributor to the As, Pb, Ni, and Cd in the top soil of Penang Island. Both Pearson correlation analysis and principal component analysis showed a strong positive correlation between Pb and Cd which indicated that they may be derived from a similar source. The contamination factor assessment indicates moderate contamination level for Pb and Ni and no element enrichment level for As and Cd. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.